3-Hydroxybutyrate Ameliorates the Progression of Diabetic Nephropathy - Jeeyoun Jung; Woo Yeong Park; Yun Jin Kim; Mikyung Kim; Misun Choe; Kyubok Jin; Ji Hae Seo; Eunyoung Ha (MDPI AG, 2022)
Studies report beneficial effects of 3-hydroxybutyrate (3-OHB) on the treatment of type 2 diabetes and obesity, but the effects of 3-OHB on diabetic nephropathy have not been elucidated. This study was designed to investigate the efficacy and mechanism of 3-OHB against progression of diabetic nephropathy (DN). Mice (db/db) were fed normal chow, high-fat, or ketogenic diets (KD) containing precursors of 3-OHB. Hyperglycemia was determined based on random glucose level (≥250 mg/dL). Fasting blood glucose and body weights were measured once a week. Twenty four-hour urine albumin to creatinine ratio was determined 5 weeks after the differential diet. Energy expenditure was measured 9 weeks after the differential diet. Body weights were significantly lower in the KD group than those in other groups, but no significant differences in fasting blood glucose levels among three groups were observed. Urine albumin to creatinine ratio and serum blood urea nitrogen (BUN) to creatinine ratio in the KD group were significantly lower than in other groups. Histologic and quantitative analysis of mesangial area suggested that KD delayed the progression of DN phenotype in db/db mice. Metabolic cage analysis also revealed that KD increased energy expenditure in db/db mice. In vitro studies with proximal tubular cells revealed that 3-OHB stimulated autophagic flux. 3-OHB increased LC3 I to LC3 II ratio, phosphorylation of AMPK, beclin, p62 degradation, and NRF2 expression. Moreover, we found that 3-OHB attenuated high glucose-induced reactive oxygen species (ROS) levels in proximal tubular cells. In vivo study also confirmed increased LC3 and decreased ROS levels in the kidney of KD mice. In summary, this study shows in both in vivo and in vitro models that 3-OHB delays the progression of DN by augmenting autophagy and inhibiting oxidative stress.